Systematic Literature Review: The Importance of Using Social Media (YouTube) on Tertiary Students' Learning Improvement in Timor-Leste - Magno Ximenes, Salvador (Journal of Information System and Education Development, 2025)
The integration of social media through YouTube now draws extensive worldwide interest for use in educational practice. YouTube serves as a beneficial educational resource in Timor-Leste by helping improve learning at the tertiary level because traditional teaching materials are not easily accessible. This review examines how YouTube enhances educational success for Timor-Leste's tertiary students. The research investigation reveals vital aspects which cover accessibility together with student engagement as well as independent learning methods yet the analysis also addresses digital competency limitations and network resource problems. The research indicates that YouTube serves as a powerful learning enhancement platform through its available multidimensional content that keeps students engaged. Optimal use of YouTube educational resources demands solution of connectivity problems and skill deficiencies in digital learning methods. The paper finishes by providing concrete advice for teachers and policy leaders who want to make full use of YouTube for education purposes at the tertiary course level.